Peningkatan Kemandirian Siswa tentang Martabat Manusia melalui Model PBL di SMK Negeri 2 Huruna - Tandroimano Laia; Hartutik Hartutik; Sugiyana Sugiyana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The main issue faced by Grade X students of SMKN 2 Huruna is the lack of learning independence, particularly in the subject Human Dignity as the Image of God. This problem is caused by the use of conventional teaching methods that are less engaging and do not encourage active student participation. As a result, student learning outcomes remain low and do not meet the expected learning objectives. This study aims to improve learning outcomes and foster student independence through the application of the Problem Based Learning (PBL) model. The research focuses on strengthening the independence dimension within the Pancasila Student Profile (P3), particularly in the affective aspect. This classroom action research (CAR) uses a quantitative approach and was conducted in two cycles. Each cycle includes four stages: planning, implementation, evaluation, and reflection. The research subjects consisted of 11 students in Grade X. Data were collected through observations of student behavior (specifically critical thinking and independence) and achievement tests conducted at the end of each cycle. The results show that the PBL model effectively improved cognitive achievement, with the average learning score rising from 80.14 in the first cycle to 83.36 in the second cycle. The percentage of students categorized as “proficient” increased from 18% to 36%. Furthermore, student independence also improved, as indicated by increased participation in discussions, confidence in expressing opinions, and the ability to complete tasks independently. The reflection stage concludes that PBL is effective in enhancing both academic performance and student independence and recommends continued support to strengthen the affective dimension of student learning.